THE CONTRIBUTION OF VOCABULARY MEMORIZATION IN MUHADATSAH LEARNING AT MAS MEDAN - Rahma, Siti; Yulia, Fatma (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This study aims to explore the contribution of vocabulary memorization (mufrodat) to the learning of Arabic conversation (muhadatsah) at MAS Muhammadiyah 1 Medan. Difficulties in learning muhadatsah remain a dominant issue among students. Many of them are unable to engage in basic conversations due to weak vocabulary mastery. Some students even struggle to memorize fundamental vocabulary, which should serve as a primary foundation in muhadatsah practice. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis follows the Miles and Huberman model, consisting of three main stages: data reduction, data display, and conclusion drawing. The findings indicate that vocabulary memorization contributes meaningfully to muhadatsah learning, as reflected in the following aspects: (1) improving memory retention through repetition; (2) building students confidence in speaking Arabic; (3) supporting long-term vocabulary storage; (4) increasing motivation to learn Arabic; (5) fostering the habit of speaking Arabic; and (6) enriching students' active vocabulary. Thus, muhadatsah becomes an effective strategy in supporting vocabulary memorization and enhancing students overall language skills.Keywords: Contribution, Mufrodat, Muhadatsah